Protection of The Rights of Rohingya Children as Refugees in Indonesia From The Perspective of International Law And Indonesian National Law - Lina Yulia Nopiyanti; Muh. Risnain; Diva Pitaloka (Mataram Journal of International Law, 2024)
This research aims to analyze the forms of human rights (HR) protection for Rohingya ethnic refugee children. Additionally, it examines the implementation of human rights protections. This study employs normative legal research using a statutory approach, utilizing secondary data sourced from literature studies, documents, and expert views. The protection of human rights for Rohingya refugee children is regulated in various international conventions, covering the most fundamental (non-derogable) rights, including the right to education, health, freedom of religion, and others. Measures to protect the human rights of the refugee children involve legal steps that adopt several legislative policies related to child protection, including refugee children, as well as steps to engage in international cooperation with organizations like the UNHCR (United Nations High Commissioner for Refugees) and IOM (International Organization for Migration).